Prevalência de demência e fatores associados em idosos institucionalizados - Siqueira, Márcia de Oliveira (2020)
Aging is multifactorial, progressive and continuous, characterized by physiological and neuropsychosocial changes, including dementia. Dementia is characterized by declines in memory, in reasoning and in daily activities, reflecting on their autonomy. The objective of this dissertation is to determine the prevalence of dementia and sociodemographic conditions in institutionalized elderly. This is a cross-sectional population-based study, which was part of the Project entitled “Patterns of Aging and Longevity: biological, educational and psychosocial aspects of Institutionalized Elderly People”, with approval by the Ethics Committee under opinion number 2,097,278 and funded by CAPES, under notice ProcaD n ° 71/2013. 474 elderly people, of both sexes residing in Long-Term Care Institutions (LTCI) in the municipalities of Passo Fundo, Carazinho and Bento Gonçalves/RS-Brazil participated in the study. All elderly people aged 60 years or over and who accept to participate in the study were included. Exclusion criteria were elderly people who were infected with infectious diseases in an acute period, seriously ill or hospitalized on the day of the meeting with the research team. The present study was necessary to assess the prevalence of dementia in elderly people living in long-term care facilities. The information contained in blocks A (identification data), B (socio-demographic variables), C (cognitive evaluation), G (health conditions) and J (functional evaluation) of a semi-structured questionnaire were used. For statistical analysis, the Poisson Regression test with robust variance was used, considering p≤0.05 as significant, and also the descriptive analysis. Most of the sample was female (71.5%) with a mean age of 80.27% ± 9.75 years. The prevalence of dementia was 49.78% in institutionalized elderly, and the factors associated with the dependent variable were living in a private LTCI, not receiving visits from family members, having a stroke, having fecal incontinence, dysphagia, low score on the Mini Mental State Examination and functional dependence (p≤0.05). Conclusion: The prevalence of dementia in institutionalized elderly people was high, especially in those who live in private institutions, do not receive visits from family members, have stroke, fecal incontinence, dysphagia, low score on the Mini Mental State Examination and functional dependence.